Companion planting to attract pollinators increases the yield and quality of strawberry fruit in gardens and allotments - Griffiths‐Lee, Janine; Nicholls, Elizabeth; Goulson, Dave (Ecological entomology, 2020)
1. Global pollinator declines have led to concern that crop yields might fall as a result of a pollination deficit. Companion planting is a traditional practice thought to increase yield of insect pollinated crops by planting a co‐flowering species next to the crop. 2. Using a combination of conventional researcher‐led experiments and observational citizen scientist data, we tested the effectiveness of bee‐friendly borage (Borago officinalis) as a companion plant to strawberry (Fragaria x ananassa). Insect visitors to the ‘Test’ (strawberry + borage) versus ‘Control’ (strawberry only) plants were observed, and strawberry fruit collected. Strawberries collected during the researcher‐led experiment were also subject to fruit measurements and assessments of market quality. 3. Companion plants were found to significantly increase both yield and market quality of strawberries, suggesting an increase in insect pollination per plant. Test strawberries companion planted with borage produced an average of 35% more fruits, and 32% increased yield by weight. Test strawberry plants produced significantly more fruit of higher aesthetic quality when assessed by Marketing Standards for Strawberries. 4. Although there was no significant difference in the overall insect visits, when broken down by broad insect group there were significantly more flies visiting the test strawberries than controls. 5. These results could have implications for both gardeners and commercial growers. As consumers prefer a cosmetically perfect fruit, the production of fruit with increased aesthetics aids food waste reduction. Using researcher‐led and citizen scientist data, the effectiveness of companion planting borage with strawberries was tested, with significantly more flies attracted to the strawberry plant. Companion planting resulted in a 35% increase in strawberry fruits, 32% yield by weight and also significantly more fruit of higher aesthetic quality when assessed by Marketing Standards for Strawberries. These results could have implications for both gardeners and commercial growers, and also helps establish a simple yet effective protocol for pollination experiments involving citizen scientists.